Louis Sullivan, James Carter, and William Kennedy
Louis Sullivan, James Carter, and William Kennedy have a conversation during a reception held at the Duke President’s house. Dr. Lou Sullivan was Secretary of Health & Human Services during the H.W. Bush administration. Dr. James Carter was a professor in the Duke Department of Psychiatry.